Microleakage in Class V Cavities Restored with Sandwich Technique: Self- Etch versus Total-Etch Bonding Systems - Panahandeh, Narges; Sheikholeslamian, Mahsa; Farzaneh, Hossein (Journal of Dental School, 2019)
Objective: Microleakage has always been a problem in restorative dentistry. To decrease microleakage, modern bonding systems, different application methods and sandwich technique have been recommended. The purpose of this study was to assess the microleakage in class V cavities restored with open sandwich technique using self-etch and total-etch bonding systems. Methods: In this in vitro study, class V cavities were prepared on the buccal and lingual surfaces of 20 extracted sound human third molars and restored with sandwich technique. Fuji II LC glass ionomer (GI) was applied to the cavity floor. After curing, half the cavities received Single Bond and the other half, Clearfil SE Bond application and were all restored with Z250 composite resin. Specimens were immersed in 2% fuchsin solution for 24 hours. After copious water irrigation, specimens were sectioned and evaluated under a stereomicroscope to determine microleakage. Data were analyzed using the Mann-Whitney U test (p<0.05). Results: The microleakage at the GI-composite interface was less than that at the occlusal and gingival margins; but this difference was not significant. No significant difference was found in microleakage between the two bonding agents in neither of the two layers. Conclusion: The etch & rinse and self-etch systems are similar in terms of microleakage.